The Kinetics Of The Dissolution Of Colloidal Silver In Cyanide Medium And Application To The Control Of The Cyanidation Process - M. J. Nicol (The Southern African Institute of Mining and Metallurgy, 1998)
The kinetics of the dissolution of colloidal silver in aerated cyanide solutions has been investigated with the aim of developing a relatively rapid and convenient method for monitoring the ?leaching power? of solutions typically used in the cyanidation process. Experimental results obtained are consistent with an electro-chemical model, in which the mixed potential is set up in the active region of the polarization curve for the anodic dissolution of silver, giving rise to a rate of dissolution which is controlled by the rate of mass transport of either cyanide or oxygen to the surface of the silver. The rate of dissolution of colloidal silver was found to respond to variations in the reactant concentrations in a similar manner to gold (and silver) in a typical free-milling ore. The use of this technique for the monitoring and control of the cyanide leach process is discussed.